DNA sequence and units of transcription of the conjugative transfer gene complex (trs) of Staphylococcus aureus plasmid pGO1. - Morton, T M (1993)
The conjugative transfer genes of 52-kb staphylococcal R plasmid pGO1 were localized to a single BglII restriction fragment and cloned in Escherichia coli. Sequence analysis of the 13,612-base transfer region, designated trs, identified 14 intact open reading frames (ORFs), 13 of which were transcribed in the same direction. Each ORF identified was preceded by a typical staphylococcal ribosomal binding sequence, and 10 of the 14 proteins predicted to be encoded by these ORFs were seen when an E. coli in vitro transcription-translation system was used. Functional transcription units were identified in a Staphylococcus aureus host by complementation of Tn917 inserts that abolished transfer and by Northern (RNA) blot analysis of pGO1 mRNA transcripts. These studies identified three complementation groups (trsA through trsC, trsD through trsK, and trsL-trsM) and four mRNA transcripts (trsA through trsC [1.8 kb], trsA-trsB [1.3 kb], trsL-trsM [1.5 kb], and trsN [400 bases]). No definite mRNA transcript was seen for the largest complementation group, trsD through trsK (10 kb). Comparison of predicted trs-encoded amino acid sequences to those in the data base showed 20% identity of trsK to three related genes necessary for conjugative transfer of plasmids in gram-negative species and 32% identity of trsC to a gene required for conjugative mobilization of plasmid pC221 from staphylococci.